Compreensão de leitura na abordagem cognitiva: uma revisão sistemática da literatura - Mariano, Clarissa Camilo (2022)
This research aimed to carry out a systematic review of the literature on Reading Comprehension, published in Brazilian journals, between 2012 and 2021, with the purpose of a) mapping recent Brazilian research on reading comprehension with a focus on the cognitive sciences of reading; b) classifying them according to the type of methodology and for empirical research articles categorizing them based on the scope of investigation, whether the article focuses on decoding or comprehension skills; c) characterizing the participants of the empirical research, identifying which year of Elementary Education they belong to, as well as if there are possible differences in performance between the female and male genders; d) seeking to identify the characteristics of reading comprehension assessment systems (tests and questionnaires) of empirical research articles and interventions that can be pedagogically reproduced; and e) pointing out potential areas for the development of the theme. To meet the stated objectives of this research, a search was carried out in the Scientific Electronic Library Online (Scielo) and the Periodicals in Psychology (Pepsic) databases. The bibliographic survey found sixty-one (61) articles, twenty (20) of which were eligible for the corpus of this work. The results indicate that studies on the reading comprehension of Elementary School II students are still incipient; research aimed at a pedagogical intervention program has ample scope for development, including research on how reading comprehension progresses between school years and between genders; that it is essential to develop evaluations of reading comprehension with greater validity; and that it is necessary to promote dialogue between the educational field and the areas of studies to which they are affiliated, such as Cognitive Psychology, so that there is greater exchange and expansion of evidence-based knowledge